مظاهر استخدام الصيرفة الالكترونية في العراق "دراسة حالة على مجموعة من المصارف التجارية في بغداد" (المجلة العراقية للعلوم الاقتصادية, 2018)
The electronic banking has been entered the field of Iraqi banking sector since 2005 , but it's still in it's beginning , but they may face some obstacles and risks which impede their work .This study aims at identifying and exploring the essence and the nature of electronic banking services provided by Iraqi commercial banks, moreover , it attempts to analyze and evaluate the obstacles, risks and elements for the prosperity of electronic banking in Iraq , to achieve the aim of this study , it has been using data collection tools from the questionnaire directed to the managers and employees of all specialists in online banking for selected sample of Iraq banks operating business in Baghdad and after analyzing the result using a statistical analysis "spss" program , the study has been reached numbers of conclusions , the most important of which there are some obstacles and risks such as lack of familiarity with e-service customers , non to provide an environmentally technical infrastructure , the absence of regulations to protect dealers which limiting the use of electronic banking, the study concluded with some recommendations , such as the need to expand the use of electronic banking for all Iraq commercial banks , moreover , the need to spread the publication of electronic banking culture between banking customers . Keywords; e-banking , electronic banks , ATM , credit cards , internet banks.